2008
DOI: 10.1210/en.2008-0975
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Insulin-Like Growth Factor II Receptor Induces Mitochondrial-Dependent Apoptosis through Gαq and Downstream Calcineurin Signaling in Myocardial Cells

Abstract: In previous studies, we have found that IGF-II and IGF-II receptor (IGF-IIR) dose dependently correlated with the progression of pathological hypertrophy after complete abdominal aorta ligation, which may play a critical role in angiotensin II-induced cardiomyocyte apoptosis. However, the detail mechanisms of IGF-IIR in the regulation of cell apoptosis in response to IGF-II remain unclear. By using IGF-IR short hairpin RNA to inhibit IGF-IR expression and using Leu27 IGF-II analog to activate specifically the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
5
58
2
Order By: Relevance
“…28) After Ang II stimulation, intracellular Ca 2þ accumulation alters mitochondrial membrane permeability, leading to a release of cytochrome c into the cytoplasm and subsequent apoptotic cascades in neonatal rat ventricular myocytes. 25) AOF is one of the most important traditional Chinese medicines, and is reported to be a neuro-protective agent. [29][30][31][32][33] It is used to treat patients with various symptoms accompanying hypertension and cerebrovascular disorders in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28) After Ang II stimulation, intracellular Ca 2þ accumulation alters mitochondrial membrane permeability, leading to a release of cytochrome c into the cytoplasm and subsequent apoptotic cascades in neonatal rat ventricular myocytes. 25) AOF is one of the most important traditional Chinese medicines, and is reported to be a neuro-protective agent. [29][30][31][32][33] It is used to treat patients with various symptoms accompanying hypertension and cerebrovascular disorders in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…23) Insulin-like growth factor II (IGF-II) also contributes by stimulating neonatal rat ventricular myocyte or H9c2 cell hypertrophy, apoptosis and remodeling. [24][25][26][27] Our previous study found that Ang II appeared to evoke IGF-II and IGF-IIR through the ERK and the JNK signaling pathway respectively, and further to activate cardiac cell apoptosis via calcineurin dependent pathways, 28) ultimately causing heart failure.…”
mentioning
confidence: 99%
“…According to its conventional role, IGF-IIR functions as a death receptor or a tumor suppression gene involved in the cytotoxic T cell-induced apoptosis and tumorigenesis (Motyka et al, 2000;Leboulleux et al, 2001). In the heart, the IGF-IIR disruption leads to cellular protection against cardiomyocyte apoptosis (Chen et al, 2004) and IGF-II and IGF-IIR up regulation in cardiomyocytes have been identified in a variety of heart disease models (Lee et al, 2006;Chang et al, 2008;Chu et al, 2008Chu et al, , 2009b. IGF-IIR could also function as a G proteincoupled receptor to trigger its downstream signaling modulators such as PKC-a/CaMKII, calcineurin and MMP/ TIMP, contributing to heart failure progression (Chang et al, 2008;Chu et al, 2008Chu et al, , 2009aChen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There were several reports explaining that exercise training depressed transcription of TTN gene in mammalian skeletal muscles (Lehti et al 2007;Velders et al 2008), and these results might be consistent with our current study. On the other hand, the IGF2R-dependent signaling pathway was suspected to be involved in the induction of cell apoptosis in the myocardium (Chu et al 2009). Overall, the physiological significance(s) of the decrease in the transcription level of TTN and IGF2R genes is still unclear.…”
Section: Genes That Were Affected Significantlymentioning
confidence: 99%